Search for Bs0 → μ+μ - and Bd0 → μ+μ - decays in pp̄ collisions at √s = 1.96 TeV - Acousta, D; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; Aoki, M; et al. (2004)
The decay mechanisms of Bs0 → μ +μ- and Bd0 → μ +μ- in pp̄ collisions were investigated. For discrimination of the decays from background events, four variables were used such as invariant mass of muon pair, B-candidate proper decay length, opening angle between B-hadron flight direction and B-candidate track isolation. A 'blind' analysis technique was also used for determination of optimal selection criteria for four variables. The results show that optimal set of selection criteria uses ∓80 MeV/c2 search window around B s0 mass, and I > 0.65.